Pengaruh Kedalaman yang Berbeda terhadap Pertumbuhan dan Tingkat Kelangsungan Hidup Kerang Mutiara (Pinctada maxim) dengan Sistem Terintegrasi di Perairan Teluk Ekas Kabupaten Lombok Timur - Mumu Sri Maulana Albayani; Muhammad Junaidi; Andre Rachmat Scabra (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2022)
Integrated cultivation is a cultivation activity that combines several commodities that have different trophic levels, pearl oysters can be a commodity to absorb organic matter because they are filter feeders. With this system, the condition of the bay's waters is ex-fertile. So that the location can be a location for pearl oyster cultivation because it has abundant food availability for pearl oysters and this greatly affects its growth and survival. The availability of this food is influenced by the depth factor. The purpose of this study was to determine the optimal depth to produce maximum granules, both in terms of quality and quantity in Ekas Bay waters. This study used 4 treatments (1, 5, 10, and 15 m) with 4 replications, for 45 days. The parameters measured were absolute length growth, specific length growth rate, absolute weight growth, specific weight growth rate, and survival of pearl oyster spat (Pinctada maxima). The results showed that the ANOVA test results of absolute length growth, specific length growth rate, absolute weight growth, specific weight growth rate, and survival of pearl oyster spat (Pinctada maxima) showed significantly different results (P<0.05). The optimal depth for growth and survival of pearl oyster spat (Pinctada maxima) in Ekas Bay waters is at a depth of 5 m (P2) with an absolute length growth of 9.05 mm, a specific length growth rate of 1.43%/day, an absolute weight growth of 0.32 g, specific weight growth rate of 6.26%, and survival rate of 76%. So it can be concluded that different depths (1, 5, 10, 15 m) have a significant effect on the growth and survival of pearl oysters (Pinctada maxima) in Ekas Bay waters.